Tools and methods for management system processes validation - N. A. Shichkov (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. One of the most difficult aspects that organizations face when implementing international management system standards is understanding and meeting the requirements related to the validation of processes for producing products or providing services.Goal. The article discusses tools and methods for validating processes for producing products or providing services.Materials and methods. Groups of management system processes are considered that require periodic “validation” - checking the process for its ability to achieve planned results. The main factors and indicators that influence the ability of production processes or service delivery processes to achieve planned results are considered. An algorithm for validating processes for producing products or providing services is considered.Results and discussion. Processes that require periodic “validation” include: so-called “special” processes, processes for the provision of services, as well as processes whose results are verified through random inspection (large-scale production and production of materials).Conclusion. Validation of management system processes should be carried out regularly at specified intervals to ensure that the process continues to achieve the required results.